Information system model for sustainable marine resource management in the Blue Village - Setiawan, Awan; Yulianto, Erwin; Dewi, Deshinta Arrova; Ilman, Benie (International Journal of Innovative Research and Scientific Studies, 2025)
This research develops, implements, and evaluates the Blue Village model, an integrated, community-based digital system for sustainable marine resource management in Mundu Pesisir Village, Cirebon, Indonesia. Using a transdisciplinary approach, the model combines GIS, IoT, socio-economic surveys, and blockchain-based funding within a participatory digital platform. Mixed-methods analysis employed spatial analytics, statistical tests, machine learning, and thematic coding. Local youth were trained as GIS operators to ensure community involvement and sustainability. Results showed a 75% decrease in illegal fishing, coral reef health improvement (index 56 to 78), and a 40% rise in fisher household income. The model also strengthened stakeholder coordination and data-driven policy-making. Despite initial digital literacy barriers, active community and youth participation were key to success. The Blue Village model effectively integrates technology with local knowledge under participatory governance, offering a scalable and replicable solution for inclusive marine governance. Practical implications include guidance for policymakers, NGOs, and coastal communities in using digital platforms to enhance conservation, stakeholder empowerment, and sustainable livelihoods, aligning with broader marine sustainability goals.